Risks of subsequent contralateral fractures of the trochanteric region in elderly - Pogliacomi, Francesco; Pellegrini, Andrea; Tacci, Fabrizio; Pedrini, Martina Francesca; Costantino, Cosimo; Pedrazzini, Alessio; Pedrazzi, Giuseppe; Lauretani, Fulvio; Vaienti, Enrico; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2017)
Background: Fractures in elderly are always a dramatic event and the healing is often not complete. In a context of bone fragility, repeated fractures are a growing problem in the industrialized world, in which the mean age of population is increasing. The aim of this study was to identify those general factors which may increase the risk of subsequent trochanteric fractures after an initial lesion. Materials and methods: Three-hundred and thirty-one patients who underwent intramedullary fixation for trochanteric fractures between January 2012 and December 2013 were studied. Forty subjects yet alive (group 1), affected by a subsequent contralateral hip fracture, were compared with 202 patients (group 2) affected by isolated trochanteric fracture. Days of hospitalization before surgery, hospitalization, period of rehabilitation, type of discharge and comorbidities, that are reported in literature as possible risk factors for hip refracture, were analyzed. In addition, all patients were interviewed in order to assess if a therapy for osteoporosis was prescribed after the initial fracture and how their gait had been modified by fractures. Results: Days of hospitalization before surgery, hospitalization, period of rehabilitation and type of discharge were not predictive factors for subsequent fractures, as well as diabetes mellitus, hypertension and cardiac diseases. The presence of neurologic and respiratory diseases were associated to a higher risk of refractures, as well as the absence of specific medical treatment for osteoporosis. Conclusions: Neurologic and respiratory comorbidities and the absence of osteoporosis medical treatment are the variables associated to a higher risk of contralateral fractures. Physicians can do more in terms of prevention and strategies must consider these risk factors.